Parasellar T2 Dark Sign on MR Imaging in Patients with Lymphocytic Hypophysitis - Nakata, Y.; Sato, N.; Masumoto, T.; Mori, H.; Akai, H.; Nobusawa, H.; Adachi, Y.; Oba, H.; Ohtomo, K. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: MR imaging findings of LYH and pituitary adenomas are similar, but the therapeutic strategies are completely different. The purpose of this study was to evaluate sellar and parasellar MR imaging findings in patients with both diseases, as well as characteristic clinical findings. MATERIALS AND METHODS: Clinical findings, including endocrinologic study and MR images of 20 patients with LYH and 22 patients with pituitary adenoma, were retrospectively reviewed. We evaluated the MR images in relation to the following: 1) the PPHI on T1-weighted images, 2) thickened stalk (>3.5 mm), 3) pituitary symmetry, 4) pituitary enhancement pattern, 5) a dural tail, and 6) parasellar signal intensity on T2- and T1-weighted images. RESULTS: Between patients with LYH and those with pituitary adenoma, a significant difference was identified for the number of patients with loss of PPHI, thickened stalk, pituitary symmetry, homogeneous enhancement, and parasellar dark signal intensity on T2-weighted images by statistical analysis (Fisher exact probability test, P < .05). Among them, only parasellar dark signal intensity on T2-weighted images had no false-positive cases. CONCLUSIONS: The parasellar T2 dark sign can be a specific finding used to distinguish pituitary adenoma from LYH. ACTHadrenocorticotrophic hormoneALanterior lobeDIdiabetes insipidusDpdesmopressinFSHfollicle-stimulating hormoneGcglucocorticoidGHgrowth hormoneGHsGH-secretingICAinternal carotid arteryIgG4immunoglobulin 4IsoisointenseLleftLHluteinizing hormoneLtlevothyroxineLYHlymphocytic hypophysitisMRIMR imagingNon-fnonfunctioningPApituitary adenomaPan-hypopanhypopituitarismPartial-hyperpartial hyperpituitarismPartial-hypopartial hypopituitarismPLposterior lobePPHIposterior pituitary T1 high intensityPRLprolactinPRLsPRL-secretingRrightsyndsyndromeT1WIT1-weighted imagingT2WIT2-weighted imagingTstestosteroneTSHthyroid-stimulating hormone